2004
DOI: 10.1016/j.phr.2004.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Outpatient Utilization for Waterborne Pathogenic Illness following Hurricane Floyd

Abstract: SYNOPSISObjectives. Flooding provides an opportunity for epidemics of waterborne viral, protozoan, or bacterial diseases to develop in affected areas. Epidemic levels of disease may translate into higher than average levels of health services use, depending in part on help-seeking behaviors. The authors investigated whether the flooding that occurred as a result of Hurricane Floyd in September 1999 was associated with an increase in outpatient visits for waterborne diseases among Medicaid enrollees in eastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Within five weeks of landfall, the proportion of visits to treatment facilities for diarrhea remained significantly higher than pre-storm levels at an ECF, 80 the RR for visiting an ECF for diarrhea was elevated (RR: 2.0; 95% CI, 1.4-2.8) compared to a same week in the previous year, 79 and a community survey found a slightly higher risk of diarrhea in two of four storm-affected areas (Area 1 OR: 1.6; 95% CI, 1.52-1.65 and Area 2 OR: 1.3; 95% CI, 1.21-1.32) compared to the previous two years 84 . In the long-term, atypical and significant increases were seen in the incidence of acute diarrhea and dysentery in the eight months after a storm, 85 and the average number of cases utilizing health services for intestinal infections doubled in the year after storm landfall (6.5 cases/month to 13.1 cases/month; P<.01) 86 . Alternatively, two surveillance system studies and one ECF study found no change in gastrointestinal illnesses in the post-storm period 78 …”
Section: Resultsmentioning
confidence: 98%
“…Within five weeks of landfall, the proportion of visits to treatment facilities for diarrhea remained significantly higher than pre-storm levels at an ECF, 80 the RR for visiting an ECF for diarrhea was elevated (RR: 2.0; 95% CI, 1.4-2.8) compared to a same week in the previous year, 79 and a community survey found a slightly higher risk of diarrhea in two of four storm-affected areas (Area 1 OR: 1.6; 95% CI, 1.52-1.65 and Area 2 OR: 1.3; 95% CI, 1.21-1.32) compared to the previous two years 84 . In the long-term, atypical and significant increases were seen in the incidence of acute diarrhea and dysentery in the eight months after a storm, 85 and the average number of cases utilizing health services for intestinal infections doubled in the year after storm landfall (6.5 cases/month to 13.1 cases/month; P<.01) 86 . Alternatively, two surveillance system studies and one ECF study found no change in gastrointestinal illnesses in the post-storm period 78 …”
Section: Resultsmentioning
confidence: 98%
“…10, 127, 129, 130, 132, 133, 135, 141, 144, 148, 163 Many studies also report higher diarrhea rates in flood-affected compared to unaffected groups, 58, 138, 139, 142, 145, 147 although two studies did not detect such a difference. 134, 137 Some studies report exposure-response effects, with increasing contact with flood waters 140, 146 or flood depth 139 associated with increased risk of diarrhea.…”
Section: Resultsmentioning
confidence: 99%
“…Two well-studied examples of 20th-century environmental injustice in the United States, in Anniston, Alabama, and Hyde Park, Georgia, both involved predominantly black communities contaminated and sickened in part by ditches bearing water laced with toxic industrial waste [179,180]. Recently, hog waste lagoons associated with industrial swine facilities in eastern North Carolina have proved resistant to regulation despite repeated flooding during hurricanes and tropical storms and persistent strong detrimental effects on the health and quality of life of neighbors, who are disproportionately black and low in income [181,182]. Thus, what artificial aquatic systems go unregulated may say as much about what we socially undervalue as what we ecologically undervalue.…”
Section: Interactions Between Perception and Condition In Artificial mentioning
confidence: 99%